Trêjidī : sāhityamāṃ ne jīvanamāṃ - Pateḷa, Cī. Nā. (Cīmanabhāī Nā.), 1918- (Gujarātī Sāhitya Parishada, 1978)
On the concept of Tragedy; includes a comparison of the western concept with similar concepts in Sanskrit poetics; revised version of the author's lectures delivered at Ahmedabad, 1975.